Skrining Kesehatan Sebagai Upaya Pencegahan Dini Penyakit Tidak Menular: Health Screening as an Early Prevention Effort for Non-Communicable Diseases - Maulid, Fika; Ulfa, Maria; Asiah, Nur; Harkensia, Linur Steffi (Chakra Brahmanda Lentera Institute, 2025)
Non-communicable diseases (NCDs) are the leading cause of death in Indonesia, with a steadily increasing prevalence. Early detection through community screening is a strategic effort to reduce the risk of NCD complications. This activity aims to detect NCD risk factors through health checks and provide education to residents of Beurandeh Village. The community service program was conducted in Beurandeh Village, Aceh Besar, during May 2025. A total of 46 residents participated in the activity, which included education and blood pressure, blood glucose, and uric acid screenings. The screening data were analyzed descriptively. Of the 20 residents screened, 24% were diagnosed with hypertension, 5% with hyperglycemia, and 19% with hyperuricemia. Interviews revealed risk factors such as excessive coffee consumption, smoking, stress, and a diet high in coconut milk. The results demonstrate the importance of screening and education in raising public awareness of NCDs. This activity also strengthened the synergy between educational institutions and the community in fostering a healthy lifestyle.